Salinity and High Temperature Tolerance in Mungbean [Vigna radiata (L.) Wilczek] from a Physiological Perspective - HanumanthaRao, Bindumadhava; Nair, Ramakrishnan M.; Nayyar, Harsh (Frontiers in Plant Science, 2016)
Biotic and abiotic constraints seriously affect the productivity of agriculture worldwide. The widely acknowledged benefits of legumes in cropping systems—biological nitrogen fixation, improving soil physical conditions and diversification of cereal-based agroecologies—are needed now more than ever. Legume production is affected by unfavorable environmental conditions, especially soil salinity and high temperatures. Among legumes, mungbean has acceptable intrinsic tolerance mechanisms, but many agro-physiological characteristics of the Vigna species remain to be explored. Mungbean has the distinct advantage of being a short duration crop, and it can grow in a range of soils and environments, as a solo or as a relay crop. This review focuses on salinity and high temperature stresses on mungbean grown as a fallow crop (mungbean-rice-wheat to replace fallow-rice-wheat) and/or a relay crop in cereal cropping systems. Salinity tolerance involves a complex of responses at the molecular, physiological, and whole plant levels. Under high temperatures, adaptation of physiological and biochemical processes gradually may lead to the development of heat tolerance; the plant acclimatizes or adapts to heat stress. At the field level, managing or manipulating cultural practices can mitigate adverse effects of salinity and high temperature. Greater understanding of the physiological and biochemical mechanisms regulating these two stresses will contribute to an evolving profile of the genes, proteins, and metabolites responsible for mungbean survival. We focus on abiotic stresses in legumes in general and mungbean in particular, and highlight gaps that need to be bridged through future mungbean research. Recent findings largely from physiological and biochemical fronts are examined, along with a few agronomic and farm-based management strategies to mitigate stress under field conditions.